Democratic Party Platform Summary of Women's Issues (1976)
This document, titled "Democratic Women's Agenda '76," summarizes women's issues included in the Democratic Party platform. It highlights economic priorities such as enforcing equal opportunity and affirmative action laws, promoting equal pay, expanding small business opportunities for women, addressing tax inequities, and supporting flexible and part-time work. The platform also calls for government reform through non-discrimination in civil service hiring and greater recruitment of women and minorities to government positions. Under government and human needs, it supports ratification of the Equal Rights Amendment, implementation of Title IX, federally funded day care, opposition to a constitutional ban on abortion, and elimination of discrimination in federal programs. The document also lists key issues not included in the platform, such as detailed national health benefits, expanded family planning research, explicit reproductive autonomy language, and ending discrimination based on sexual or affectional preference.